Fabrication of high surface area graphene electrodes with high performance towards enzymatic oxygen reduction. (10th February 2016) - Di Bari, Chiara; Goñi-Urtiaga, Asier; Pita, Marcos; Shleev, Sergey; Toscano, Miguel D.; Sainz, Raquel; De Lacey, Antonio L.
Graphical abstract: Abstract: High surface area graphene electrodes were prepared by simultaneous electrodeposition and electroreduction of graphene oxide. The electrodeposition process was optimized in terms of pH and conductivity of the solution and the obtained graphene electrodes were characterized by X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy and electrochemical methods (cyclic voltammetry and impedance spectroscopy). Electrodeposited electrodes were further functionalized to carry out covalent immobilization of two oxygen-reducing multicopper oxidases: laccase and bilirubin oxidase. The enzymatic electrodes were tested as direct electron transfer based biocathodes and catalytic currents as high as 1 mA/cm 2 were obtained. Finally, the mechanism of the enzymatic oxygen reduction reaction was studied for both enzymes calculating the Tafel slopes and transfer coefficients.